2013
DOI: 10.1007/s12539-013-0151-3
|View full text |Cite
|
Sign up to set email alerts
|

Identifying novel oncogenes: A machine learning approach

Abstract: Genome sequencing has overflowed the databases with huge amount of SNP data. Although the amount of detected single nucleotide polymorphisms (SNPs) is rising exponentially every day, we still lag behind in characterization techniques. Implementing computational platforms to determine the pathogenecity associated with the SNPs can provide a probable solution to this problem. To improve the prediction quality for SNP characterization methods, we implemented machine learning support vector classification method. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 30 publications
0
17
0
Order By: Relevance
“…Most of these studies focus on the correlation of CTC enumeration with prognosis 913. However, recent studies showed that only enumerated CTCs were not enough to reflect the heterogeneous condition of tumors 3,14,15.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies focus on the correlation of CTC enumeration with prognosis 913. However, recent studies showed that only enumerated CTCs were not enough to reflect the heterogeneous condition of tumors 3,14,15.…”
Section: Introductionmentioning
confidence: 99%
“…Further exploration of their correlations with clinicopathological variables as well as their diagnostic and prognostic values were conducted. Centromere Protein L (CENPL) is a component of the CENPA-CAD (nucleosome distal) complex, which participated in the assembly process of kinetochore proteins, mitotic progression and chromosome segregation 26 . Interferon stimulated exonuclease gene 20 Like 2 (ISG20L2) encodes a 3'-5' exoribonuclease that involved in the 12S pre-rRNA processing, as a target gene of miR-139-3p, has been reported to take part in the pathogenesis of hepatocellular carcinoma 27,28 .…”
Section: Discussionmentioning
confidence: 99%
“…Centromere Protein L (CENPL) is a component of the CENPA-CAD (nucleosome distal) complex, which participated in the assembly process of kinetochore proteins, mitotic progression and chromosome segregation [57]. Interferon Stimulated Exonuclease Gene 20 Like 2 (ISG20L2) encodes a 3'-5' exoribonuclease that involved in the 12S pre-rRNA processing, as a target gene of miR-139-3p, has been reported to take part in the pathogenesis of hepatocellular carcinoma [58,59].…”
Section: Discussionmentioning
confidence: 99%